1987
DOI: 10.1128/jvi.61.7.2162-2170.1987
|View full text |Cite
|
Sign up to set email alerts
|

Site-directed mutagenesis of proteinase 3C results in a poliovirus deficient in synthesis of viral RNA polymerase

Abstract: We used a synthetic double-stranded oligonucleotide to introduce amino acid substitutions into the proteinase 3C region of a poliovirus type 1 cDNA clone. The six different mutant viruses recovered exhibited a small-plaque phenotype when assayed on HeLa cells. Further investigation revealed that all the mutations (with the exception of one) yielded P3 region proteins that displayed altered mobility in sodium dodecyl sulfatepolyacrylamide gel electrophoresis. A conservative Val-* Ala change at amino acid 54 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Since poliovirus encodes its own proteinases, we tested to see if mutations in a viral proteinase would affect the formation of complex III. Poliovirus mutant Sel3C-02 (kindly provided by Dr Bert Semler) has a site-directed valine to alanine substitution at amino acid 54 of the poliovirus 3CPro gene (Dewalt and Semler, 1987). This virus produces less of the viral-encoded RNA dependent RNA polymerase (3DP°l) than wild-type poliovirus and very little 3CPro.…”
Section: Resultsmentioning
confidence: 99%
“…Since poliovirus encodes its own proteinases, we tested to see if mutations in a viral proteinase would affect the formation of complex III. Poliovirus mutant Sel3C-02 (kindly provided by Dr Bert Semler) has a site-directed valine to alanine substitution at amino acid 54 of the poliovirus 3CPro gene (Dewalt and Semler, 1987). This virus produces less of the viral-encoded RNA dependent RNA polymerase (3DP°l) than wild-type poliovirus and very little 3CPro.…”
Section: Resultsmentioning
confidence: 99%
“…This arrangement of /~-strands is compatible with recently reported data on site-directed and random mutagenesis of this protease. Specifically, substitution of Val or Ala for GIy 51 (hereafter in this section the poliovirus numbering is used), presumably disrupting a/~-turn, was lethal, whereas substitution of Asp (a residue frequently occurring in flturns [23]) in the same position resulted in a viable virus [24]. Substitutions in strands E and F which could cause local deformations of the/3-sheet exerted relatively mild effects on viral reproduction [24][25][26], and a substitution of Ser for Cys 153 in strand J appeared to be without effect on the activity of 3C P'° expressed in E. coli [9].…”
Section: A Chymotrypsin-like Structural Fold In 3c Pr°mentioning
confidence: 99%
“…Specifically, substitution of Val or Ala for GIy 51 (hereafter in this section the poliovirus numbering is used), presumably disrupting a/~-turn, was lethal, whereas substitution of Asp (a residue frequently occurring in flturns [23]) in the same position resulted in a viable virus [24]. Substitutions in strands E and F which could cause local deformations of the/3-sheet exerted relatively mild effects on viral reproduction [24][25][26], and a substitution of Ser for Cys 153 in strand J appeared to be without effect on the activity of 3C P'° expressed in E. coli [9]. Moreover, the processing defects inflicted by substitutions in strands E and F were similar (namely, impairment of the cleavage at the C-terminus of 3C Pr° itself [24,25]), in accord with our proposal that these strands might interact with each other in native 3C Pt°.…”
Section: A Chymotrypsin-like Structural Fold In 3c Pr°mentioning
confidence: 99%
See 1 more Smart Citation
“…A final maturational cleavage occurs in the assembled virion by an unknown mechanism. Studies of chimeric and mutant picornaviruses have demonstrated that interruption of 3C proteolytic processing prevents the formation of new virions (Dewalt & Semler, 1987;Kean et al, 1988Kean et al, , 1990Dewalt et al, 1989Dewalt et al, , 1990Mirzayan et al, 1991).…”
mentioning
confidence: 99%